ANALISIS KEPUTUSAN PEMBELIAN SMARTPHONE SAMSUNG DI KOTA SURABAYA: Insights into Samsung Smartphone Consumer Choices in Surabaya - Abu Rizal Nawawi; Hetty Murdiyani (Archetype : Jurnal Ilmiah Psikologi dan Terapan, 2025)
This study aims to analyze the influence of motivation and emotions on the purchase decision of Samsung smartphones in Surabaya. Motivation is defined as the internal drive of consumers to fulfill their needs or desires, while emotions encompass positive feelings that affect brand preferences. The study employs a quantitative approach with a survey method, involving 200 respondents who purchased Samsung smartphones within the past year. Data were collected using a Likert-scale questionnaire and analyzed using multiple linear regression to examine the relationships between variables. The findings indicate that motivation significantly influences purchase decisions, with social status needs and self-actualization emerging as key factors. Moreover, emotions positively affect purchase decisions, particularly through feelings of pride and happiness when using the product. The interaction between motivation and emotions strengthens consumers’ decisions to choose Samsung smartphones over other brands. This study provides implications for marketing strategies, suggesting that companies should emphasize emotional aspects and consumer needs in promotional campaigns. By understanding the factors influencing consumer behavior, Samsung can enhance customer loyalty and strengthen its market position. Keywords: Motivation, Emotion, Purchase Decision, Samsung Smartphones, Surabaya Consumers.